The growth and unique electronic properties of the porous-alumina-assisted hafnium-oxide nanostructured films. (10th December 2019) - Bendova, Maria; Pytlicek, Zdenek; Prasek, Jan; Mozalev, Alexander
Abstract: Hafnium-oxide nanostructures of controlled composition and properties are in demand for modern electronic and optical engineering. Here hafnium-oxide nanostructured films are synthesized on substrates via the anodizing/re-anodizing of a thin Hf layer through a porous anodic alumina (PAA) film at 150/400 V in 0.2 m  H3 PO4 electrolyte and examined by SEM, EIS, and Mott-Schottky analysis. The films are composed of HfO x nanorods, which grow in the pores, anchored to a continuous HfO2 bottom layer by tiny HfO x nanoroots penetrating the alumina barrier layer. The understanding of film nucleation and growth is advanced through disclosing the hidden features and field-assisted modifications of the metal-oxide interfaces, such as O2 -filled nanosized voids and individual hafnium-oxide nanoroots dominating within the alumina barrier layer and securing electron transport to each nanorod. The films reveal a unique combination of electrical properties, such that the bottom oxide behaves like an ideal dielectric whereas the roots and rods show semiconducting behavior. A 600 °C annealing at atmospheric pressure surprisingly leaves the rods and roots semiconducting and still amorphous while the annealing at 10 −5  Pa transforms the entire film to a nanocrystallite-containing n- type semiconductor, of a high doping density of up to 2 10 21  cm −3 . Further anodic polarization of the PAA-free vacuum-annealed film generates dielectric anodic oxide over the film, of thickness proportional to applied potential until the thinner roots and finally the dominating root become fully blocked for electron conduction. Potential applications include high-k dielectrics for high-voltage electrolytic capacitors, semiconducting active layers for gas sensing, or photoanodes for photoelectrochemical water splitting. Graphical abstract: Image 1012430 Highlights: Arrays of HfO x nanostructures via anodizing Al/Hf metal layers on substrates. Anodizing responses, SEM, CV, EIS, Mott-Schottky analysis. Revealing the missing features of PAA-assisted hafnium oxide growth. Tuned film properties: dielectrics, semiconductors, combination of both. Potential application to energy storage, gas-sensing, solar water splitting.